Effects of Research-Based Science Learning on Students' Critical Thinking Skills: A Bibliometric Analysis - Rahmadini Lasonia Putri; Andani Intan Ridha Illahi; Sylvia Muharani Ulmi; Fauziah Ulmi; Asrizal Asrizal (Jurnal Penelitian Pembelajaran Fisika, 2025)
In the era of industrial revolution 4.0, 21st century skills such as critical thinking, collaboration, communication and creativity have become essential for individual success in an ever-evolving work environment. There is an urgency to conduct research on the effects of research-based learning in improving students' critical thinking skills, which can provide a strong foundation for learners to succeed in a dynamic and complex future. This study utilized bibliometric research method. Articles were searched using the keywords “Critical Thinking; Research Based Learning”. The search included patterns of trends in scholarly publications related to the exploitation and protection of river turtle populations, as well as patterns in author relationships between relevant articles. Data were analyzed and visualized using VOS viewer software. Results Visualization analysis of journals on research-based learning highlighted that topic such as “research samples” and “worksheets” dominated the literature, reflecting consistency in the development of research-based learning practices in the classroom.